Advanced Lung Cancer Inflammation Index Predicts Outcomes of Patients With Colorectal Cancer After Surgical Resection. Issue 9 (September 2020) - Kusunoki, Kurando; Toiyama, Yuji; Okugawa, Yoshinaga; Yamamoto, Akira; Omura, Yusuke; Ohi, Masaki; Araki, Toshimitsu; Kusunoki, Masato
Abstract : BACKGROUND: The advanced lung cancer inflammation index is considered a useful prognostic biomarker of clinical outcomes in patients with malignancies. However, the prognostic value of the advanced lung cancer index in patients with colorectal cancer who underwent surgical resection remains unclear. OBJECTIVE: In this study, we evaluated the prognostic value of the advanced lung cancer index in patients with colorectal cancer. DESIGN: Prospectively obtained data of patients with colorectal cancer were retrospectively evaluated to clarify the clinical relevance of the advanced lung cancer index. SETTINGS: We conducted this study at a single expert center. PATIENTS: We enrolled 298 patients with colorectal cancer who underwent surgical resection in this retrospective study. MAIN OUTCOME MEASURES: The primary outcome was the clinical relevance of the advanced lung cancer index in patients with rectal cancer. RESULTS: Low status of advanced lung cancer index was significantly correlated with undifferentiated histology ( p = 0.004), T stage progression ( p < 0.001), R1/R2 resection for primary surgery ( p = 0.004), and distant metastasis ( p < 0.001). Multivariate analysis showed that low advanced lung cancer index status was an independent prognostic factor for both overall survival (HR = 3.21 (95% CI, 1.97–5.19); p < 0.001) and disease-free survival (HR = 2.13 (95% CI, 1.23–3.63); p = 0.008) in patients with colorectal cancer. Furthermore, the clinical burden of the advanced lung cancer index was consistent between sexes, and its prognostic value was verified in patients with clinically relevant stage III colorectal cancer. LIMITATIONS: The present study had several limitations, including retrospective observation and a small sample size of Japanese patients from a single institution. CONCLUSIONS: The advanced lung cancer index could be a useful prognostic indicator of clinical outcomes in patients who underwent surgical resection for colorectal cancer. See Video Abstract at http://links.lww.com/DCR/B267 . EL ÍNDICE AVANZADO DE INFLAMACIÓN DEL CÁNCER DE PULMÓN, PREDICE LOS RESULTADOS DE LOS PACIENTES CON CÁNCER COLORRECTAL DESPUÉS DE LA RESECCIÓN QUIRÚRGICA: ANTECEDENTES: El índice avanzado de inflamación del cáncer de pulmón, es considerado como un útil biomarcador pronóstico, en los resultados clínicos de pacientes con neoplasias malignas. Sin embargo, aún no está claro el valor pronóstico del índice avanzado de cáncer de pulmón, en pacientes con cáncer colorrectal sometidos a resección quirúrgica. OBJETIVO: Evaluar el valor pronóstico del índice avanzado del cáncer de pulmón, en pacientes con cáncer colorrectal. DISEÑO: Los datos obtenidos prospectivamente de pacientes con cáncer colorrectal, fueron evaluados retrospectivamente, para aclarar la relevancia clínica del índice avanzado del cáncer de pulmón AJUSTE: Estudio realizado en un solo centro experto. PACIENTES: Estudio retrospectivo, incluyendo 298 pacientes con cáncer colorrectal, sometidos a resección quirúrgica. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue la relevancia clínica del índice avanzado de cáncer de pulmón, en pacientes con cáncer rectal. RESULTADOS: Un índice avanzado de cáncer de pulmón bajo, se correlacionó significativamente con la histología indiferenciada ( p = 0.004), la progresión de la etapa T ( p <0.001), la resección R1 / R2 para cirugía primaria ( p = 0.004) y la metástasis a distancia ( p <0.001). El análisis multivariante mostró que el índice avanzado de cáncer de pulmón bajo, era un factor pronóstico independiente, tanto para la supervivencia general (HR = 3.21 IC 95% 1.97-5.19 p <0.001) como para la supervivencia libre de enfermedad (HR = 2.13, IC 95% 1.23-3.63, p = 0, 008), en pacientes con cáncer colorrectal. Además, la carga clínica del índice avanzado de cáncer de pulmón, fue consistente entre los sexos y su valor pronóstico se verificó clínicamente relevante, en pacientes con cáncer colorrectal en estadio III. LIMITACIONES: El presente estudio tuvo varias limitaciones, incluyendo la observación retrospectiva y la pequeña muestra de pacientes japoneses, en una sola institución. CONCLUSIONES: El índice avanzado de cáncer de pulmón, podría ser un indicador pronóstico útil, en los resultados clínicos de pacientes sometidos a resección quirúrgica por cáncer colorrectal. Consulte Video Resumen http://links.lww.com/DCR/B267 . Abstract : Supplemental Digital Content is available in the text.